RNA-seq transcriptional atlas for the rat - Bush, S (University of Oxford, 2021)
This dataset supports the publication "Generation and network analysis of an RNA-seq transcriptional atlas for the rat" by Summers, et al. It comprises two text files, one (zipped) containing raw data (n = 7666 RNA-seq libraries), and one containing the median downsampled TPM for each of 25,013 genes, averaged for tissue, age, and BioProject (n = 590 averaged samples). Methods are described in the associated publication but in brief are as follows. For each library, expression was quantified using Kallisto v0.44.0. Kallisto quantifies expression at the transcript level, as transcripts per million (TPM), by building an index of k-mers from a non-redundant set of Ensembl and NCBI reference transcripts and then ‘pseudo-aligning’ reads to it, matching k-mers in the reads to k-mers in the index. Transcript-level TPM estimates were then summed to give gene-level TPM. Prior to expression quantification, and for the purpose of minimising variation between samples, we randomly downsampled all libraries to 10 million reads, 5 times each, using seqtk v1.2. Expression level was then taken to be the median TPM across the 5 downsampled replicates. All scripts for generating the atlas are available at www.github.com/sjbush/expr_atlas.